IMPLEMENTASI PENANAMAN NILAI-NILAI NASIONALISME DI SDN KARANGANYAR GUNUNG 02, CANDISARI, SEMARANG, JAWA TENGAH - Dyah Indraswati; Deni Sutisna (Jurnal Rontal Keilmuan Pancasila dan Kewarganegaraan, 2020)
This study aims to determine the implementation of the cultivation of nationalism values and the obstacles faced by schools. This research is descriptive research with a qualitative approach. This research was conducted in January 2020 at SDN Karanganyar Gunung 02, Candisari, Semarang, Central Java. The subjects of this research were class V teachers. Data collection techniques included observation, interviews, and documentation. The research instruments used were interview guidelines, observation guidelines, and documentation guidelines. The data validity test was done by triangulation of techniques and triangulation of sources. Technique triangulation is done by checking the data using different techniques at the same source. Source triangulation is done by checking data on different sources. The data analysis technique used includes data collection, data reduction, data presentation, and drawing conclusions. The results showed that SDN Karanganyar Gunung 02 had implemented the implementation of the value of nationalism in learning activities through exemplary and inserting character values into the subject matter being taught. SDN Karanganyar also implements the values of nationalism outside of learning activities such as extracurricular activities. The obstacle in planting the values of nationalism is that teachers still find it difficult to integrate the values of nationalism in the lesson plans but in practice, it has been done. The second obstacle is the difficulty in adapting the curriculum to local wisdom. The implication of this research is as a reference for educators to see the challenges and obstacles in the implementation of planting the values of nationalism so that it can be used to improve aspects that are not yet optimal.Keywords: implementation; the value of nationalism; resistance